Impact of Sex on Clinical Response in Rheumatoid Arthritis Patients Treated With Biologics at Approved Dosing Regimens. (3rd December 2020) - Fang, Lanyan; Song, Xuyang; Ji, Ping; Wang, Yaning; Maynard, Janet; Yim, Sarah; Sahajwalla, Chandrahas; Xu, Mingjiang; Kim, Myong‐Jin; Zhao, Liang
Abstract: The prevalence of rheumatoid arthritis (RA) is higher in females than in males. With the development of new treatment options and strategies such as biologics, we found it worthwhile to identify whether males and females warrant different treatment regimens to ensure the best clinical response. Our meta‐analysis included 11 clinical trials of RA patients in support of the Food and Drug Administration's approval of 6 biological products. We evaluated the data of American College of Rheumatology 20 (ACR20) 24 or 26 weeks after treatment. Logistic regression models were applied to compute the odds ratio (OR) of treatment responses between sexes. The ORs of ACR20 response rates in males and females were similar across all studies and not significantly different in overall studies (OR, 1.05; 95% confidence interval, 0.96‐1.16) analyzed with a fixed‐effects model. Further analyses on the 7 ACR20 subcomponents showed high heterogeneity among studies (Q statistic P < .00007, I 2 > 95%), with no observed clinically meaningful sex‐related difference. Thus, our meta‐analysis did not find significant difference in ACR20 response rates between male and female RA patients treated with biologics at approved dosing regimens. This result supports the current clinical practice of not requiring sex‐dependent treatment regimens for RA patients.